Aldosterone defects in infants and young children with hyperkalemia: A single center retrospective study - Liu, Xu; Xie, Yanshu; Tang, Jing; Zhong, Jingzi; Zeng, Dan; Lan, Dan (Frontiers in Pediatrics, 2023)
Introduction: Hyperkalemia is a rare but severe condition in young children and usually discovered as a result of hemolysis of the blood samples taken. However, patients with defects in either aldosterone biosynthesis or function can also present with hyperkalemia- as well hyponatremia-associated, and metabolic acidosis. It is a challenge to make an accurate diagnosis of these clinical conditions. We conducted this study to investigate the clinical and genetic features of aldosterone signaling defects associated hyperkalemia in young children. Method: A retrospective review was conducted at the pediatric department of the First Affiliated Hospital of Guangxi Medical University from 2012 to 2022. Results: 47 patients with hyperkalemia were enrolled, of which 80.9% (n=38) were diagnosed with primary hypoaldosteronism, including congenital adrenal hyperplasia due to 21-hydroxylase deficiency (n=32), isolated hypoaldosteronism (n=1) due to CYP11B2 gene mutation and Xp21 contiguous gene deletion syndrome (n=1). Additionally, 4 patients were clinically-diagnosed with primary adrenal insufficiency. Nine patients were confirmed with aldosterone resistance, of which one child was diagnosed with pseudohypoaldosteronism (PHA) type 1 with a mutation in the NR3C2 gene and 3 children were identified with PHA type 2 due to novel mutations in either the CUL3 or KLHL3 genes. Five patients had PHA type 3 because of pathologies of either the urinary or intestinal tracts. Conclusions: The etiologies of infants with hyperkalemia associated with aldosterone defects were mostly due to primary hypoaldosteronism. An elevated plasma aldosterone level may be a useful biomarker for the diagnosis an aldosterone functional defect in patients presented with hyperkalemia. However, a normal plasma aldosterone level does rule out an aldosterone defect in either its biosynthesis or function, especially in young infants. Molecular genetic analyses can greatly help to clarify the complexity of disorders and can be used to confirm the diagnosis.